Antidiabetic Mechanisms of Fruits - Ali Fattahi PhD; Fatemeh Niyazi PharmD; Behzad Shahbazi PharmD; Mohammad Hosein Farzaei PhD; Gholamreza Bahrami PhD (SAGE Publishing, 2017)
Rosa canina fruits have been used traditionally for the treatment of diabetes mellitus and its complications. The aim of current study was to evaluate the in vitro mechanism of action of R canina in managing diabetes mellitus. Cell proliferation and cytotoxicity assay were performed on pancreatic β-cells, βTC6. The protective activity of the extract on streptozotocin-induced death in βTC6 cells was studied. The effect of R canina on the metabolism of glucose in HepG2, a hepatocellular carcinoma cell line, was evaluated. The effect of the extract on glucose diffusion across the dialysis membrane, which is a comfortable model for assessing cellular glucose absorption, was evaluated. The results obtained from current study confirmed that R canina extract can act as a growth factor for pancreatic β-cell line providing a novel mechanism for the observed antidiabetic effect of this natural agent. Further preclinical studies are necessary to evaluate the perfect mechanism of action of R canina in diabetes mellitus.